Pupil-linked arousal signals track the temporal organization of events in memory - David Clewett (Nature Portfolio, 2020)
Although everyday life unfolds continuously, we tend to remember past experiences as discrete events. Here, the authors show that dynamic, pupil-linked arousal states track the encoding of such episodes, as revealed by changes in memory for the temporal order and duration of recent event sequences.